2021 IEEE EMBS International Conference on Biomedical and Health Informatics (BHI) 2021
DOI: 10.1109/bhi50953.2021.9508619
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Deep Learning based Cerebral Palsy Prediction with Channel Attention

Abstract: The theme of IEEE-EMBS BHI-BSN 2021 is "Reshaping healthcare through advanced AI-enabled health informatics for a better quality of life". The joint program (BHI-BSN) will have worldrenowned speakers from academic and research institutes, government agencies, and industry. It will provide a unique forum to showcase enabling technologies of devices and sensors, hardware and software systems, predictive models, databases, and big data analytics and machine learning that optimize the acquisition, transmission, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…For our model, one video is classified as F+ if the video level score got by Top-K strategy is greater than 0.5 in the seen video. For STAM [18], MS-G3D [15], Zhu et.al [27], the classification threshold is set to 0.5. Since action detection tasks also include classification, we also report the video-level performance of WOAD [7] and W-TALC [19].…”
Section: Resultsmentioning
confidence: 99%
“…For our model, one video is classified as F+ if the video level score got by Top-K strategy is greater than 0.5 in the seen video. For STAM [18], MS-G3D [15], Zhu et.al [27], the classification threshold is set to 0.5. Since action detection tasks also include classification, we also report the video-level performance of WOAD [7] and W-TALC [19].…”
Section: Resultsmentioning
confidence: 99%
“…• Conv2D-1, Conv2D-2 [7]: They are two 2D convolutional neural networks, each of them consists of two 2D convolutional layers with differences in the output channel sizes. • CANet [9]: This method proposes a 2D convolutional neural network with the squeeze-and-excitation channel attention module. The whole system is proposed for the CP classification task on the MINI-RGBD dataset.…”
Section: B Comparing With State-of-the-art Methodsmentioning
confidence: 99%
“…In order to evaluate the robustness of our system and other state-of-the-art DNN-based methods [9], [20], [21], we simulate different datasets by adding different levels of Gaussian noise to the infant joint The noise level is divided into four levels from 15% standard deviation to 120% standard deviation of each infant's joint pose data. The tests results are displayed in Fig.…”
Section: F Robustness Testmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it difficult to discover inter-joint correlations that are important for capturing coordination among different joints of human gait from raw joint features. We also observed that the majority of existing work only applies DL on individual joint features such as the time series of joint positions [23,28]. As a consequence, these methods usually perform sub-optimally on smaller-scale medical datasets.…”
Section: Introductionmentioning
confidence: 93%